PROBLEMS WITH CLEAN WATER SOURCES FOR COASTEL COMMUNITIES IN KUALA LANGSA VILLAGE, ACEH PROVINCE - Susi Mulianti Lubis; Riska Tia Pratiwi; Inka Farahdina; Shally Rezeki (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2022)
Public perception, clean water, PDAM